Fruit-filies in coffee cultivars in Presidente Prudente, SP - Montes, Sônia Maria Nalesso Marangoni; Raga, Adalton; Souza- Filho, Miguel Francisco; Strikis, Pedro C.; dos Santos, Pedro César (Coffee Science - ISSN 1984-3909, 2012)
Coffee is considered the primary host of the Mediterranean fruit fly Ceratitis capitata (Wiedemann). The infestation of C. capitata in the State of São Paulo has reached economic importance in coffee plantations. Although little information about changes caused by the fly on the coffee beverage, it is known that the fruit fly infestation causes rapid change from “cherry” to “raisin” stage, causing qualitative damage on the parchment coffee production. The objective of this work was to study the population dynamics and diversity of Tephritidae and Lonchaeidae in coffee cultivars of Icatu Vermelho IAC 4045, Vermelho IAC 99, Novo Mundo 388-17-1, Obatã IAC 1669-20, Icatu Amarelo IAC 2944, grafted on Apoatã (IAC 2258) (Coffea canephora) and Icatu Vermelho IAC 4045 ungrafted and Apoatã (IAC 2258)-grafted with approximately 3 years. The experiment was conducted in Presidente Prudente, São Paulo State, Brazil, from June 2006 to July 2008. The experimental design was a randomized block with four replications in a factorial design (3 years X 6 cultivars). From each plot of 100 plants we randomly collected 250 mature fruits. The samples were taken at 15 day intervals. The population dynamics were evaluated by using one plastic McPhail trap per cultivar. After 26 months a total of 36,932 specimens of C. capitata were trapped in all cultivars, corresponding to 49.27% males and 50.73% females. Approximately 83.3% of the specimens were collected from January to December 2007. The population fluctuation showed population peaks in May, June and July, relative to fruit ripening period. We trapped 21 specimens of A. montei Lima and A. fraterculus (Wied.). The coffee fruits of Presidente Prudente, SP, are infested by the following species of Lonchaeidae: Neosilba pendula (Bezzi), N. zadolicha McAlpine & Steyskal, N. inesperata Strikis & Prado and Neosilba pradoi Strikis & Lerena. Neosilba pendula occurred in all evaluated cultivars and N. inesperata was recoverd only from Icatu Amarelo IAC 2944 and IAC Icatu Vermelho 4045/un-grafted. No Anastrepha specimen was recovered from the fruits. Cultivars did not differ due to tephritid and lonchaeid infestations, but in 2008 the highest infestation by C. capitata occurred in the field.